Effect of Aluminum Incorporation on the Reaction Process and Reaction Products of Hydrated Magnesium Silicate - Jia, Yuan; Zou, Yuxin; Zou, Xinmei; Jiang, Yaoting; Li, Fangyuan; Ma, Wangkun; Yan, Hongli; Hua, Rui (Frontiers in Materials, 2022)
In this study, we investigated the impact of aluminium ion (Al3+) incorporation on the microstructure and the phase transformation of the magnesium silicate hydrate system. The magnesium silicate hydrate system with aluminium was prepared by maxing magnesium oxide and silica fume with different aluminium ion contents (the Al/Si molar ratios of 0.01, 0.02, 0.05, 0.1, 0.2) at room temperature. The high degree of polymerization of the magnesium silicate hydrate phases resulted in the limited incorporation of aluminium in the structure of magnesium silicate hydrate. Aluminum, the silicon-oxygen tetrahedra sites of magnesium silicate hydrate layers, however, was unable to substitute for silicon sites through inverted silicon-oxygen linkages. The increase in aluminium ion content raised the degree of polymerization of the magnesium silicate hydrate phases from 0.84 to 0.92. A solid solution was formed from residual aluminum-amorphous phases such as hydroxyl-aluminum and magnesium silicate hydrate phases. X-ray diffraction (XRD), field emission scanning electron microscope (F-SEM), 29Si and 27Al MAS NMR data showed that the addition of Al3+ promotes the hydration process of MgO and has an obvious effect on the appearance of M-S-H gel. The gel with low aluminum content is fluffy, while the gel with high aluminum content is irregular flake. The amount of Al3+ that enter M-S-H gel increased with the increase of Al3+ content, but there was a threshold, the highest Al/Si molar ratio of M-S-H gel can be maintained at about 0.006.